Electromagnetic measurements in the near field - Bienkowski, Pawel (SciTech Pub., 2012)
The book reviews developments in the following fields: electromagnetic measurement; near field; far field; electric field measurement; magnetic field measurement; power density measurement; directional pattern synthesis; and photonic EMF measurement.
Revised edition of: Electromagnetic field measurements in the near field / Hubert Trzaska. c2001.
Keywords: Electromagnetic fields -- Measurement.; elektronické knihy; electronic books